Inhibitory effect of Aphidicolin - a tetracyclic diterpene - on the proliferation and apoptotic induction in human cervical cancer (HeLa) cells - Yu, En-Yan; Zhao, Rui-Yan; Wang, Dong-Sheng (Journal of B.U. ON., 2015)
The objective of the present work was to investigate the antitumor and apoptotic effect of aphidicolin against human cervical cancer (HeLa) cells. Flow cytometry was performed to detect alterations in the mitochondrial membrane potential loss (ΔΨm) after aphidicolin treatment. Cell viability was assessed by the MTT assay while the apoptotic effects of the compound were examined by fluorescence microscopy and flow cytometry. Aphidicolin induced dose-dependent as well as time-dependent cytotoxic effects in HeLa cells. Chromatin condensation and formation of apoptotic bodies were observed by Hoechst 33258 staining after drug treatment. Aphidicolin induced both early and late apoptosis in HeLa cells which were correlated with strong concentration of the compound. ΔΨm was also observed following aphidicolin treatment at varying doses. Aphidicolin is a potent antitumor and apoptotic agent against human cervical carcinoma and its effects are mediated via chromatin condensation and mitochondrial membrane potential loss.